Theory and Empirics of Short-Time Work: A Review - Natalia Bermudez; Muriel Dejemeppe; Giulia Tarullo (Global Labor Organization (GLO), 2023)
Following massive take-up rates during the COVID-19 period, short-time work (STW) policies have attracted renewed interest. In this paper, we take stock of this policy instrument and provide a critical review of STW systems in Europe. We focus on the objectives of STW programs and their primary characteristics, as well as the inefficiencies associated with these policies, such as excessive use and slower worker reallocation. Additionally, we take a stroll through the main contributions of STW impact evaluations. Finally, we identify relevant directions for the refinement of the main design features of the scheme, key lessons, and avenues for future research.
Keywords: E24; J22; J23; J63; J65; 330; Short-time work; labor hoarding; employment; firm survival; unemployment insurance